Behavior of an embankment on soft deposit improved by column-link method - J.C. Chai; J. Ni; M.D. Liu (International Association of Lowland Technology, 2020)
The behavior of a test embankment on soft deposit improved by column-link method in Saga, Japan, was investigated by three dimensional (3D) finite element analysis (FEA). In column-link method, the column-walls under the shoulders of an embankment are linked by geogrids or cables to restrict lateral movement of the walls and partially reduce the embankment settlement. A geogrid with a tensile strength of 36 kN/m and yielding strain of 12% was used and relatively large lateral displacement of about 0.18 m occurred. The results of FEA showed that the geogrid might yield. The results indicated that to effectively restrain lateral movement of the walls, geogrids with high tensile strength and stiffness, like steel cables were needed. With the conditions of the test embankment, using steel cables, the mobilized tensile force in the cable could reach more than 600 kN/m. Further, at the upper part of the column walls, high compression or tensile stresses could be developed with strong linking geogrids. Thus, reinforcing the column walls with steel bar or H-steel is required. The results from this study showed a properly designed column-link method could be an effective and economic soft ground improvement method.